Conditions of nontrivial solvability of the homogeneous Dirichlet problem for equations of any even order in the case of multiple characteristics without slope angles - Buryachenko, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We consider the homogeneous Dirichlet problem in the unit disk $K ⊂ R^2$ for a general typeless differential equation of any even order $2m,\; m ≥ 2$, with constant complex coefficients whose characteristic equation has multiple roots $± i$. For each value of multiplicity of the roots $i$ and $–i$, we either formulate criteria of the nontrivial solvability of the problem or prove that the analyzed problem possesses solely the trivial solution. A similar result generalizes the well-known Bitsadze examples to the case of typeless equations of any even order.